1989
DOI: 10.3109/02713688909000030
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of purified monoclonal antibody needed to prevent HSV-1 induced stromal keratitis in mice

Abstract: A purified IgG2a monoclonal antibody with a neutralizing titer of 10(4) and specificity for gD was evaluated for its therapeutic potential in a murine ocular infection model. BALB/c mice, infected on the scarified cornea with 10 times the HSV-1 strain RE concentration needed to produce severe and persistent stromal opacity, were given a single inoculation of antibody intraperitoneally 24 hours later. The animals were then followed for corneal disease development. Antibody, at concentrations as low as 10 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 15 publications
5
31
0
Order By: Relevance
“…We have argued previously that in non-immune animals the extensive centrifugal spread of virus back to the eye is likely to contribute significantly to the later development of severe ocular damage such as irreversible corneal opacity (Dyson et al, 1987). Hence in passively immunized mice the restricted spread of infection in the nervous system seems the most likely explanation for the absence of such damage, that we and other workers (Metcalf et al, 1987(Metcalf et al, , 1988Raizman & Foster, 1988;Foster et aL, 1988;Thompson et al, 1988;Lausch et al, 1989) have observed in such animals.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We have argued previously that in non-immune animals the extensive centrifugal spread of virus back to the eye is likely to contribute significantly to the later development of severe ocular damage such as irreversible corneal opacity (Dyson et al, 1987). Hence in passively immunized mice the restricted spread of infection in the nervous system seems the most likely explanation for the absence of such damage, that we and other workers (Metcalf et al, 1987(Metcalf et al, , 1988Raizman & Foster, 1988;Foster et aL, 1988;Thompson et al, 1988;Lausch et al, 1989) have observed in such animals.…”
Section: Discussionmentioning
confidence: 78%
“…These clinical observations were supported by the similarity in the two groups of timing and incidence of virus isolation from eye washings and virus antigens in corneal epithelial sheets. Others have reported that passive immunization does not affect titres of virus at the inoculation site during primary infection of the eye (Lausch et al, 1989) or skin (Kapoor et aL, 1982). In contrast, if mice are actively immunized against HSV-1 some time before inoculation of the cornea virus is rapidly cleared from the tears (Tullo et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…As in to our study, the mean survival time was significantly increased. Furthermore, kinetic studies have shown that treatment with this MAb did not significantly accelerate virus clearance from the eye (Lausch et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have indicated that a single inoculation of 8D2 mcAb given intraperitoneally 24 h after infection was highly effective at preventing the development of persistent stromal dis ease [15]. An additional dose-response exper iment was carried out to determine whether our initial observations could be confirmed.…”
Section: Effect Of8d2 Mcab Treatment On Hsv-i Ocular Infectionmentioning
confidence: 99%
“…A number of years ago it was reported that xenogeneic polyclonal anti-HSV sera [12] or mouse monoclonal antibod ies (mcAbs) [13] to HSV glycoproteins could on passive transfer protect mice against en cephalitis induced by HSV following ocular infection. More recently, mcAbs specific for glycoproteins gB, gC, and gD have been found to protect at the level of the eye itself after HSV-1 infection [14,15].…”
Section: Introductionmentioning
confidence: 99%